2016
DOI: 10.1101/088864
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Ubiquity and quantitative significance of bacterioplankton lineages inhabiting the oxygenated hypolimnion of deep freshwater lakes

Abstract: Freshwater bacterioplankton in the oxygenated hypolimnion are reportedly dominated by specific members that are distinct from those in the epilimnion. However, no consensus exists regarding the ubiquity and abundance of these bacterioplankton, which is necessary to evaluate their ecological importance. The present study investigated the bacterioplankton community in the oxygenated hypolimnia of 10 deep freshwater lakes. Despite the broad geochemical characteristics of the lakes, 16S rRNA gene sequencing demons… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(24 citation statements)
references
References 91 publications
0
23
1
Order By: Relevance
“…Forty‐five (78.9%) of these genomes were of high quality, with estimated completeness and contamination scores of >80% and < 5%, respectively (Supporting Information Table S3). Consistent with previous observations (Okazaki and Nakano, ; Okazaki et al ., ), a depth‐stratified bacterioplankton community was observed – members of LD12, Actinobacteria and Cyanobacteria were dominant in the epilimnion, whereas CL500‐11 and Ca . Nitrosoarchaeum were dominant in the hypolimnion (Supporting Information Table S4).…”
Section: Resultsmentioning
confidence: 95%
See 2 more Smart Citations
“…Forty‐five (78.9%) of these genomes were of high quality, with estimated completeness and contamination scores of >80% and < 5%, respectively (Supporting Information Table S3). Consistent with previous observations (Okazaki and Nakano, ; Okazaki et al ., ), a depth‐stratified bacterioplankton community was observed – members of LD12, Actinobacteria and Cyanobacteria were dominant in the epilimnion, whereas CL500‐11 and Ca . Nitrosoarchaeum were dominant in the hypolimnion (Supporting Information Table S4).…”
Section: Resultsmentioning
confidence: 95%
“…), which is a member of the ammonia‐oxidizing, chemoautotrophic archaeal taxon Marine Group I (MGI). Members of MGI dominate the hypolimnion of deep freshwater lakes (Okazaki et al ., ) (Supporting Information Table S4) and thus are important players in the nitrogen and carbon cycles of lakes. In marine systems, members of MGI are also dominant in the deep aphotic layer, and recent studies have reported the presence of several putative MGI viruses (Chow et al ., ; Labonté et al ., ), including those encoding AMGs such as amoC (Ahlgren et al ., ) and cobS (López‐Pérez et al ., ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Lakes are physically disconnected ecosystems, and thus offer a good model for investigating the diversification and phylogeographic processes of microbes. Whereas 16S rRNA gene-based phylogenies have been used to characterize the cosmopolitan bacterioplankton lineages that are ubiquitously dominant in freshwater systems [36][37][38], analyses at finer phylogenetic resolution have been used to identify intra-lineage microdiversity and phylogeography. A global-scale investigation of microdiversity was conducted for the PnecC subcluster of the genus Polynucleobacter (Betaproteobacteria), a cosmopolitan freshwater bacterial group, using the ITS and glnA gene as markers, which showed distance-decay patterns and global-scale niche separation of subgroups adapted to different thermal conditions [15].…”
Section: Introductionmentioning
confidence: 99%
“…Cryptic microdiversification with almost identical 16S rRNA gene sequences within a ubiquitous freshwater lineage, for example, Limnohabitans and Polynucleobacter , has been reported (Jezbera et al 2011, 2013; Hahn et al 2015, 2016). Different sub‐populations were present among the lineages (e.g., acI–B1 and acI–A7) occurring in the entire water layer (Okazaki et al 2017). Coincidentally, a horizontal oligotype profile in Lake Michigan indicated oligotype differentiation between estuarine and pelagic sites (Newton and McLellan 2015).…”
Section: Discussionmentioning
confidence: 99%